PENINGKATAN KEMAMPUAN MEMBACA HURUF HIJAIYAH MELALUI PERMAINAN KARTU HURUF PADA ANAK KELOMPOK B TK ABA LABBAIK AMONG PUTRO III - Zumrotut Tachyah; Titik Mulat Widiyastuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low ability of Group B children at ABA Labbaik Among Putro III Kindergarten to read Hijaiyah letters. Initial observations indicated that most children experienced difficulties in recognizing, distinguishing, pronouncing, and reading Hijaiyah letters correctly. This study aimed to improve the ability to read Hijaiyah letters through letter card games for children aged 5-6 years. The study employed the Classroom Action Research (CAR) model developed by Kemmis and McTaggart, which consisted of two cycles involving the stages of planning, action, observation, and reflection. The research subjects were 17 children aged 5-6 years in Group B. Data were collected through observation, documentation, interviews, and performance assessment. The data were analyzed using descriptive quantitative and qualitative methods by calculating the percentage of children's achievement in reading Hijaiyah letters in each cycle. The results showed that the use of letter card games improved the children's ability to read Hijaiyah letters. In the pre-cycle stage, 35% of the children were in the not yet developed category, 53% were beginning to develop, and 12% were developing as expected. In Cycle I, there was an improvement, with 35% of the children categorized as beginning to develop, 41% as developing as expected, and 24% as developing very well. In Cycle II, a significant improvement was observed, with 18% of the children categorized as developing as expected and 82% as developing very well, exceeding the research success indicator of 75%. Based on these findings, it can be concluded that letter card games are an effective learning medium for improving the ability to read Hijaiyah letters among children aged 5-6 years at ABA Labbaik Among Putro III Kindergarten.